A comparison of psychological well-being in athlete and non-athlete women - GHORBAN HEMATI ALAMDARLOO; SETAREH SHOJAEE; ENAYATOLLAH ASADMANESH; HOMA SHEIKHANI SHAHIN; AGHDAS RANGANI; SARA NEGAHDARIFARD (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: The present study was aimed to compare psychological well-being in athlete and non-athlete women. Material/Methods: The statistical population of the present study included all athlete and non-athlete women in Shiraz, Iran. The sample consisted of 764 subjects (382 athletes, 382 non- athletes), of which the athlete and non-athlete samples were selected by Gerjesy and Morgan' sample size table and purposeful sampling method, respectively. Also, Ryff's psychological well-being scale (Ryff, 1989) was used for measuring subjects' psychological well-being. Independent t-test and multivariate analysis of variance (MANOVA) tests were used for data analysis. Results: The results showed a significant difference between athlete and non-athlete women in terms of their psychological well-being and its subscales (p<.01). Conclusions: According to this finding, it can be concluded that psychological well-being is better in athlete compared to non-athlete women. Therefore, it can be argued that sport activities are effective in improving the psychological well-being of women.